Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Number: 3
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

La naissance et la petite enfance en Nouvelle Angleterre à l'époque coloniale 1630-1750 - Bergamasco-Lenarda, Lucia (Revue d’histoire moderne et contemporaine, 1984)
Keywords: 1600-1699; 1700-1799; amériques; approches et analyses; colonialisme; colonisation britannique; condition de l'enfant; cours; discipline; enfance; famille; his4443; histoire; maternité; patriarcat; petite enfance; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis

La Femme gelée - Ernaux, Annie (Gallimard, 1981)
Professeure de trente ans, mariée à un cadre, mère de deux enfants, elle habite un appartement agréable. Pourtant, c'est une femme gelée. C'est-à-dire que, comme des milliers d'autres femmes, elle a senti l'élan, la curiosité, toute une force heureuse présente en elle se figer au fil des jours entre les courses, le dîner à préparer, le bain des enfants, son travail d'enseignante.
Section: 184 pages ; 21 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; care; corps; corps féminin; cours; discipline; europe; famille; france; justice sociale; lit301N; littérature; maternité; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; écriture des femmes*